Implementation of eMental health technologies for informal caregivers: A multiple case study - Bastoni, Sofia; van Gemert-Pijnen, Lisette; Sanderman, Robbert; van Dongen, Anne (Frontiers in Digital Health, 2023)
Informal caregivers offer continuous unpaid support to loved ones who are unable to live independently. Informal care is an essential pillar of healthcare around the world and a very prominent phenomenon in Europe, affecting over 17% of the entire population. Providing care can be a very burdensome commitment that heavily impacts informal caregivers’ mental health. eMental health technologies are a possible solution to improve caregivers’ mental health and their overall experience of caregiving. However, eMental health technologies often face challenges of implementation. The present work collects testimonies of implementation experts of eight eMental health technologies for informal caregivers with the aim of comparing them and extracting lessons learned. For this multiple case study, technologies were selected (through informal suggestions and independent search) according to the following inclusion criteria: they were intended for informal caregivers as main user group, were aimed at improving informal caregivers' mental wellbeing and caregiving experience and were available and running in real life settings in Europe. Ten interviews were conducted (two pilots and eight included cases). The interviewees were asked to provide a description of the technology and its aims and their implementation approach, method and frameworks used. Finally, and determinants of implementation, the influence of the Covid-19 pandemic on implementation processes and lessons learned were investigated. The results highlighted key differences between technologies developed within academia and the industry regarding efficacy testing and use and use and choice of frameworks. Also, similarities in terms of recognized barriers such as financing were detected. Finally, possible ways to overcome main barriers and examples of best practices were extracted, such as structuring a business model and discussing tool maintenance and long-term hosting in advance.